A comparative study between talented young Greek and German handball players in some physical and anthropometric characteristics - Galal El-Din, H.; Zapartidis, I.; Ibrahim, H. (Biology of Sport, 2011)
This international comparative study between talented young handball players in Germany and Greece investigated specific physical and anthropometric characteristics. This investigation of both elite profiles will allow us to determine the differences in the selection system for elite young handball players between the two countries. One hundred and sixty-two players participated in this study, 88 Greek young male players and 74 German young male players. For anthropometric tests the players were measured for body height, body mass and body mass index, arm span, hand length and hand spread. Physical fitness measurements were 30 m sprint, standing long jump, sit and reach flexibility, and 20 m shuttle run test. The results of this study demonstrate that Greek players were taller and heavier (p<0.01), had longer arm span and hand length (p<0.01), and performed better in 30 m sprint (p<0.01), standing long jump (p<0.01) and aerobic capacity (p<0.01). German players outperform in hand spread (p=0.03). While some of these differences can be explained by the different strategies and training methods, and also the training environment, the results do have important implications and effects in the physical condition of junior players.